(untitled) (American Journal of Research in Humanities and Social Sciences, 2024)
This study addresses the subject of “Regulations Governing Administrative Decisions in Judicial Institutions in Iraq,” with the objective of identifying the legal, procedural, and ethical standards that organize the administrative decision-making process within these institutions. The research provides an analysis of the significance of administrative decisions as a tool that enhances transparency and integrity within the judicial system, contributes to improving administrative efficiency, and ensures the protection of individual and group rights. The study also examines the challenges facing judicial institutions in Iraq, including legislative, regulatory, and environmental obstacles that hinder the effective implementation of administrative decisions. The study employs a descriptive survey research method, with data collected from a random sample of employees within judicial institutions in Baghdad to analyze the current state of these regulations. Additionally, it aims to offer practical recommendations to improve the administrative decision-making process, thereby enhancing justice and efficiency in managing the Iraqi judicial system.